Genomic Blocks in Aethionema arabicum Support Arabideae as Next Diverging Clade in Brassicaceae - Walden, Nora; Nguyen, Thu-Phuong; Mandáková, Terezie; Lysak, Martin A.; Schranz, Michael Eric (Frontiers in Plant Science, 2020)
The tribe Aethionemeae is sister to all other crucifers, making it a crucial group for unraveling genome evolution and phylogenetic relationships within the crown group Brassicaceae. In this study, we extend the analysis of Brassicaceae genomic blocks (GBs) to Aethionema whereby we identified unique block boundaries shared only with the tribe Arabideae. This was achieved using bioinformatic methods to analyze synteny between the recently updated genome sequence of Aethionema arabicum and other high-quality Brassicaceae genome sequences. We show that compared to the largely conserved genomic structure of most non-polyploid Brassicaceae lineages, GBs are highly rearranged in Aethionema. Furthermore, we detected similarities between the genomes of Aethionema and Arabis alpina, in which also a high number of genomic rearrangements compared to those of other Brassicaceae was found. These similarities suggest that tribe Arabideae, a clade showing conflicting phylogenetic position between studies, may have diverged before diversification of the other major lineages, and highlight the potential of synteny information for phylogenetic inference.